ORDERING OF GOODS IN COMPUTERIZED SYSTEM PT.ALFA RETAILINDO TBK - Setiawan Setiawan; Ir. Don Elsyafitra Ir. Don Elsyafitra (Jurnal Sistem Informasi, 2001)
With the rapid economic growth, the effect on the activity kehidupann and this causespeople to want things to run fast-paced and practical.PT.ALFA Retailindo is a dealer distributor of product variety household goods. Ineach execute a transaction is always dilakukanpencatatan reservation, to be used as adelivery report. Report delivery is beneficial for companies to find out how manyproducts have been given from the warehouse to the supplier at the time.The mechanism of recording all transactions of goods PT.Alfa Reatilindo bookingsstill use manual recording and thus require a relatively lamadibandingkan time usingcomputers, so that in making statements about the ordering of goods is facing variousconstraints.Thus the complexity of the process of ordering goods transaction, then needed asystem that can manage data effectively and efficiently reservations. Accurate dataprocessing make the leaders can analyze and then take the best step for theadvancement of the company.